2003
DOI: 10.1007/s00464-002-8502-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of holding strength of various surgical clips

Abstract: Due to advances in clip design, new types of surgical ligation clips are available that may reduce clip failure and improve function, especially for 5-mm clip appliers. We tested a preformed spring clip based on a 5-mm applier against other commonly used clips from 5- and 10-mm multiloading clip appliers. Five different clips were compared using a digital force gauge to test perpendicular pulloff force after application to tubing of varying thickness and compliance. The average pull-off force for commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Addressing the removal safety issue, it became obvious that the radial pull-off force is less than half the force needed for axial pull-off. In accordance with in vitro results, it can be concluded that the radial type of shear stress can be expected to be crucial in clip dislocation [13], [14]. The Nelson et al study using silicon tubes resulted in a 1.8-fold axial removal force compared to radial removal force and was comparable to the results of the present study in the animal model (2.2-fold).…”
Section: Discussionsupporting
confidence: 89%
“…Addressing the removal safety issue, it became obvious that the radial pull-off force is less than half the force needed for axial pull-off. In accordance with in vitro results, it can be concluded that the radial type of shear stress can be expected to be crucial in clip dislocation [13], [14]. The Nelson et al study using silicon tubes resulted in a 1.8-fold axial removal force compared to radial removal force and was comparable to the results of the present study in the animal model (2.2-fold).…”
Section: Discussionsupporting
confidence: 89%
“…Titanium clips may increase graft arterial length compared with the stapling device, but may become easily dislodged with transverse force (8,9). Multiple clinical cases of titanium clip dislodgment have been reported and have resulted in significant complications including gas embolus and hemorrhage (10)(11)(12)(13).…”
mentioning
confidence: 98%
“…9 In our study, the addition of a small pledget did not make a difference in terms of either parenchymal laceration or the holding strength of the different suture anchors.…”
Section: Discussionmentioning
confidence: 73%